'Being the culture' and 'playing the culture': Choro and the Brazilianness performed in Brussels. Issue 2 (1st October 2021) - Barbosa, Eliana Rosa de Queiroz
Choro is an instrumental Brazilian music genre that emerged in Rio de Janeiro in the nineteenth century. It can adopt various forms with a basis of guitar, flute and cavaquinho ‐ the latter, a small guitar of Portuguese origin. Musical arrangements are normally elaborate, although in Brazil the players gather in usually informal and open settings, in indoors or outdoors formations called rodas ('circles'). Following the customs of many Brazilian genres, players sit in a circle facing each other, the audience stands around and, occasionally, skilled couples dance to it. A roda de choro is not a concert, yet it is not just a rehearsal, but also a musical experience based on spontaneity. This article, drawing upon an observation exercise in the Brussels (Belgium) Choro scene, intends to explore the multitude of meanings of Choro as a practice in which Brazilians in diaspora, other migrants and locals engage and share experiences with each other, focusing on the social geographies of Choro and the social networks derived from this musical practice. The observation of this music-making process in Brussels raises additional questions of Brazilian (musical) identity in diaspora and its relation to the notions of longing (saudades), authenticity, affinity, transcendence and joy.